Adherence to disease-modifying treatments in patients with multiple sclerosis. Issue 2 (12th March 2012) - Ibarra, O.; Mora, O.; Ardanza, E.; de Torre, A. Lopez; Palacios, I.; Bustos, M.
Abstract : Background: The current treatment of multiple sclerosis is based on disease-modifying treatments, including intramuscular and subcutaneous interferon (IFN) or subcutaneous glatiramer acetate. Observational studies have shown that patient adherence to treatment is suboptimal and adherence is a key issue in chronic diseases to maximise treatment benefits. Purpose: The goal of this study was to evaluate the level of adherence to disease- modifying treatment in multiple sclerosis in our patients during 2011. Materials and methods: The study cohort consisted of patients with multiple sclerosis attended at Galdakao- Usansolo Hospital Outpatient Pharmacy. The authors conducted a retrospective analysis of pharmacy claim data from January to September of 2011, and The authors calculated the medicines possession rate to assess adherence to treatment. Percentage of patients with optimal adherence (more than 95%) was the primary outcome measured. Patients included were older than 18 years and had been on treatment for at least 6 months at the moment of analysis. Results: At the beginning of the study The authors selected for analysis 41 patients on treatment, 6 of whom started treatment during 2011 (61% female; mean age: 40.5±10.2 years). Regarding the drug, 14 patients received intramuscular IFN β-1a, 10 subcutaneous IFN β-1a, 10 subcutaneous IFN β-1b and seven glatiramer acetate. 85.4% of the patients had an adherence level greater than 95%, however 4.9% had suboptimal adherence and 9.8% discontinued the treatment during the monitoring period. They abandoned the treatment voluntarily and in one case the drug was withdrawn because the illness progressed. The mean adherence level in our cohort was 89.5%±29.9. Conclusions: Although the level of adherence in our multiple sclerosis patients during 2011 was high, The authors had almost ten percent of treatment discontinuation.